Truly Sharia Compliant? A Critical Analysis of Hotel Facilities and Management in Banda Aceh - Ahmad Kamal Al Ghifary; Muhammad Haris Riyaldi; Eddy Gunawan; Amri Amri; Khairil Umuri (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
The purpose of this study is to analyze the facilities and management at the Kumala Hotel in Banda Aceh related to the implementation of sharia principles based on the DSN-MUI Fatwa No. 108/DSN-MUI/X/2016. The background is the increasing need for Muslim tourists for accommodation that is in line with sharia in the development of hotel concepts in Aceh. The method used is a qualitative approach that uses data collection techniques through interviews, observation and documentation. The results show that the Kumala Hotel has provided halal food, prayer room and prohibit immoral acts and pornography. From the management side, sharia principles are attempted in service, human resources, and finance. However, obstacles that arise are the limited human resources who understand sharia in more depth and less than optimal supervision. It is hoped that the results of this research will be able to contribute and references in the development of sharia hotels in Indonesia.